Rapid dramatic alterations to the tumor microstructure in pancreatic cancer following irreversible electroporation ablation. (August 2014) - Zhang, Zhuoli; Li, Weiguo; Procissi, Daniel; Tyler, Patrick; Omary, Reed A; Larson, Andrew C
Aim: NanoKnife ® (Angiodynamics, Inc., NY, USA) or irreversible electroporation (IRE) is a newly available ablation technique to induce the formation of nanoscale pores within the cell membrane in targeted tissues. The purpose of this study was to elucidate morphological alterations following 30 min of IRE ablation in a mouse model of pancreatic cancer.Materials & methods: Immunohistochemistry markers were compared with diffusion-weighted MRI apparent diffusion coefficient measurements before and after IRE ablation.Results: Immunohistochemistry apoptosis index measurements were significantly higher in IRE-treated tumors than in controls. Rapid tissue alterations after 30 min of IRE ablation procedures (structural and morphological alterations along with significantly elevated apoptosis markers) were consistently observed and well correlated to apparent diffusion coefficient measurements.Discussion: This imaging assay offers the potential to serve as an in vivo biomarker for noninvasive detection of tumor response following IRE ablation. Original submitted 2 October 2012; Revised submitted 12 March 2013